(untitled) (Bangladesh Journal of Botany, 2008)
Distribution of glandular and eglandular hairs on the aerial organs of Salvia recognita Fisch. & Mey. has been investigated. Glandular hairs of S. recognita have consisted of capitate and peltate hairs. Capitate hairs were present abundantly on all aerial parts of S. recognita while peltate hairs were only present on stem, leaf, bract and calyx. Eglandular hairs were also widespread on all aerial parts. Key words: Salvia recognita, Lamiaceae, Glandular hairs, Eglandular hairs, Endemic doi:10.3329/bjb.v37i1.1571 Bangladesh J. Bot. 37(1): 93-95, 2008 (June)